4-Substituent pyridine directed cobalt(ii) azides: solvothermal synthesis, structure, and magnetic properties1. Issue 22 (14th June 2015) - Zhao, Jiong-Peng; Zhao, Cui; Song, Wei-Chao; Wang, Lei; Xie, Yabo; Li, Jian-Rong; Bu, Xian-He
<x xml:space="preserve">Abstract</x> Azido-bridged magnetic complexes: Different 4-substituent groups of pyridine co-ligands directed the linkages between azide and Co(ii) ions, to give three azide–Co(ii) complexes with different structures and magnetic properties.